The Impact of Gadget Screen Exposure in Children and Developmental Status Aged 12 - 72 Months - Endah Dian Marlina; Raudhatul Munawarah; Rosita Syaripah (Indonesian Journal of Global Health Research, 2026)
In 2023, Indonesia’s population of children under five reached 30.2 million. Current data indicates that 33.44% of early childhood individuals are exposed to digital devices, with many facing risks of psychological, cognitive, and socio-emotional impairments. Objective: This study aims to analyze the relationship between gadget screen exposure and the developmental status of children aged 12–72 months. A quantitative study with a cross-sectional design was conducted at Posyandu Puskesmas Pulo Gadung, East Jakarta, in 2025. A sample of 60 respondents was selected through purposive sampling. Data were collected using the Pre-Screening Developmental Questionnaire (KPSP) and a maternal questionnaire regarding gadget usage. Data were analyzed using univariate and bivariate (Chi-square) analysis. Bivariate analysis revealed a significant relationship between gadget exposure and developmental status ($p < 0.05$). High gadget exposure was predominantly associated with "doubtful" or "deviant" developmental outcomes. Excessive gadget use negatively impacts child development. It is crucial for health workers and parents to implement early stimulation and strict screen-time monitoring to ensure optimal growth.